2012
DOI: 10.12651/jsr.2012.1.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Current status of terrestrial mammals on Jeju Island

Abstract: Located 60 km from southern tip of Korean peninsula, Jeju is the largest Island in Korea and composed of volcanic habitat. Twenty-eight species of terrestrial mammals are listed from Jeju Island, of which 1 species and 3 subspecies are endemic. Also, 1 endangered species and 4 invasive alien species of land mammals are listed. Current status, brief history, management and conservation of the 28 species are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Siberian roe deer from Jeju Island (SKJ) showed the lowest level of genetic diversity in this study and compared to other species. This is presumably due to its geographical isolation (Jo, Kim, Choi, & Oh, ) and a small founder population originally colonizing Jeju Island. The Mainland Korea (SKM) population showed relatively high haplotype diversity and low nucleotide diversity among the populations sampled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siberian roe deer from Jeju Island (SKJ) showed the lowest level of genetic diversity in this study and compared to other species. This is presumably due to its geographical isolation (Jo, Kim, Choi, & Oh, ) and a small founder population originally colonizing Jeju Island. The Mainland Korea (SKM) population showed relatively high haplotype diversity and low nucleotide diversity among the populations sampled.…”
Section: Discussionmentioning
confidence: 99%
“…High nucleotide diversity of Siberian roe deer at the northern periphery of its geographical range in Yakutia (RYA) may belong to the former scenario as it was reported that the population there is a mixture of two subspecies, C. p. pygargus and C. p. tianschanicus (Argunov, 2013;Boeskorov & Danilkin, 1998 in this study and compared to other species. This is presumably due to its geographical isolation (Jo, Kim, Choi, & Oh, 2012) and a small founder population originally colonizing Jeju Island. The Mainland Korea (SKM) population showed relatively high haplotype diversity and low nucleotide diversity among the populations sampled.…”
Section: Genetic Diversity and Demographic Historymentioning
confidence: 99%
“…Many studies reported the disturbance of regeneration of tree species by ungulate browsing around the world (Wilson 1969, Gill 1992, Waller and Alverson 1997, Potvin et al 2003, Rooney and Waller 2003, Senn and Suter 2003, Weisberg and Bugmann 2003, Cote et al 2004, Tsujino and Yumoto 2004, Pepin et al 2006, Takatsuki 2009, Hidding et al 2012, Nagaike et al 2014Cutini et al 2015, Swiss Federal Institute for Forest 2015; a few studies were carried out on the dynamics and the other ecological issues of roe deer in Korea (Kim and Kim 2001, Kim 2006, Kim and Hong 2006, Kim et al 2007a, Jeon and Kim 2011, Jo et al 2012, 2013, Kang 2013. In addition, studies on the dynamics of forest stands indicated that competition with other species of understory vegetation such as dwarf bamboo (genus Sasa) can interrupt the establishment of the seedlings of the natural tree species at forest stands of the world (Nakashizuka 1988, Peters et al 1992, Abe et al 2001, Taylor et al 2004, 2006, Doležal et al 2009, Song et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This diminutive, charming chipmunk became a preferred pet of the Korean public and visitors to Korea to the extent that it was an important animal export of Korea until the 1980s (Yoo 2000). Unfortunately, the proclivity for T. sibiricus as a pet resulted in trapping, exporting, and transplanting large numbers beyond its natural distribution, such as Jeju Island in Korea and countries in Europe and Japan, except for Hokkaido Island with an indigenous population (Chapuis et al 2009;Oshida 2009;Jo et al 2012). Siberian chipmunks remain a highly merchandized animal in pet shops in Korea today and is an emblematic animal for "clean nature" or environmental quality in Korea.…”
Section: Introductionmentioning
confidence: 99%